Kinanthropometry in African sports: Body composition and somatotypes of world class male African middle, long distance and marathon runners - Ridder, J.; Monyeki, K.; Amusa, L.; Toriola, A.; Wekesa, M.; Carter, L.
There were significant differences (p<.05) by event group between the mean somatotypes as well as the means of the mesomorphic component where the LD (long distance) runners were significant lower in mesomorphy than the M (marathon) runners.